2018
DOI: 10.1177/2059513118765294
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for peri-traumatic distress and appearance concerns in burn-injured inpatients identified by a screening tool

Abstract: Introduction:Psychosocial screening of burn-injured patients is a National Burn Care Guideline and is increasingly used to identify individuals most in need of support. It can also generate data that can inform our understanding of patient reported concerns following a burn injury.Method:As part of routine care, 461 patients admitted to a burns unit were screened soon after admission using a psychosocial screen designed by the service. The questionnaire included items on pre-existing social support, coping, em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Psychological screening is in line with NBCS 6 and established clinical practice within burns care services. 11 Further psychology input was then delivered if required. At the time of audit, there was no established service screening tool for burns outpatients.…”
Section: Methodsmentioning
confidence: 99%
“…Psychological screening is in line with NBCS 6 and established clinical practice within burns care services. 11 Further psychology input was then delivered if required. At the time of audit, there was no established service screening tool for burns outpatients.…”
Section: Methodsmentioning
confidence: 99%
“…The second type includes pre-trauma correlates such as prior psychopathology, prior trauma exposure, familial psychiatric history, and neurobiological factors (Rosellini 10.3389/fpsyg.2022.1030470 Frontiers in Psychology 04 frontiersin.org et al, 2018). The third type concerns peri-trauma factors including the duration/severity of trauma exposure, core belief challenge, and subjective fear (Oaie et al, 2018;Meiser-Stedman et al, 2019;Beaudoin et al, 2021). The fourth type involves post-trauma factors including coping strategies, rumination, resilience, attribution style, access to needed resources, social support, specific cognitive patterns, gratitude, etc.…”
Section: Dissociation Of Relationship Grief Of Loss and Trauma Recoverymentioning
confidence: 99%
“…Previous studies have found that one of the strongest factors associated with PTSD is the presence of ASD in the acute post-injury period [12,13]. Additionally, there is no clear pattern of injury etiology or circumstance most associated with the development of stress disorder symptoms [15]. It is therefore necessary to screen patients with burn injuries for symptoms of stress disorders throughout their recovery and intervene with patients who are symptomatic.…”
Section: Introductionmentioning
confidence: 99%